The partisan press : a history of media bias in the United States - Sheppard, Si, 1972- (Jefferson, N.C. : McFarland & Co., 2008)
"Illustrates how partisan bias in the American media has built political parties, set the stage for several wars, and even contributed to the rise and fall of U.S. presidents. Discusses the rise of the unprecedented post-World War II model of objective journalism and explains why this model is breaking down in today's technology-driven media environment"--Provided by publisher.
Includes bibliographical references (p. 357-371) and index.
Keywords: Journalism -- Objectivity -- United States -- History; Press and politics -- United States -- History